Investigation of the biological active compounds of crocus sativus stigmas (saffron) from Ukraine - O. O. Mykhailenko (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Saffron, the most expensive spice in the world, comes from the Crocus sativus stigmas. Saffron grows well in the areas with the cold winters and warm dry summers, which have a positive effect on the quality of the raw material obtained. This explains the interest in saffron cultivation and production in Ukraine. Since 2015, large-scale saffron cultivation for food purposes has been started in various regions of Ukraine. Cultivation methods, environmental factors of different regions differ and directly affect on the composition and quality of biologically active compounds of raw materials. In addition, according to recent pharmacological studies, saffron stigma exhibit a wide range of biological activity: anticancer, anti-inflammatory, antidiabetic, antihypertensive, anticonvulsant and other actions that are caused by the composition of biologically active compounds of the saffron stigmas - crocin, picrocrocin and safranal. Therefore, the aim of the work was to establish the content of crocin, safranal and picrocrocin in Crocus rstigmas grown in different regions of Ukraine in accordance with the requirements of ISO 3632. For research, we used saffron stigmas (Crocus sativus L.) harvested in Kherson, Zaporizhia, Vinnytsia, Odessa, Chernihiv regions in Ukraine in October 2018 and the sample of commercial saffron from Italy (Migros Bio, 2018). The quality of the raw material was established in accordance with ISO 3632 according to the indicators: weight loss of drying, ash total, content of picrocrocin, crocin and safranal by UV-Vis spectroscopy. In the saffron samples the weight loss of during and the ash total ranged from 6.7-9.2% to 4.3-6.4%, respectively. The content of picrocrocin ( 257 нм nm) in saffron samples ranged from 90 in Kherson and up to 101 in the Chernihiv sample; safranal content ( 330 nm) ranged from 34 for Chernihiv to 42 in the Kherson sample; crocin content ( 440 nm) of 228 in Vinnitsa and up to 262 in Zaporozhye. The obtained data showed that all samples of Ukrainian saffron belong to the first quality category according to ISO classification. In the commercial sample from Italy, the test showed a high content of safranal (330 nm was 59) and crocin (440 nm was 259). Different values between regions and a commercial sample are usually due to different environmental conditions and cultivation practices. Crocus sativus is an important medicinal and food plant that has been successfully cultivated in Ukraine for food purposes and is of great economic importance. The quality of Ukrainian saffron from different regions has been determined to ISO 3632. The 2018 crop samples are in compliance with international standards and are of category I. It is important that crocin and safranal exhibit high anticancer and antioxidant activity, so growing in our country stable high content of BACs, makes it possible to use saffron not only in the food industry, but also makes it a potentially relevant raw material for the pharmaceutical industry. This study provides significant information on the quality and prospects of saffron production in Ukraine, as both the food and pharmacological raw materials.